Co-gasification of refused derived fuel and biomass in a pilot-scale bubbling fluidized bed reactor. (15th February 2020) - Pio, D.T.; Tarelho, L.A.C.; Tavares, A.M.A.; Matos, M.A.A.; Silva, V.
Highlights: Co-gasification of RDF with biomass was studied in an autothermal pilot-scale BFB. Stable conditions of operation were attained and defluidization was not observed. RDF addition led to enhanced gasification products and producer gas LHV increase. RDF is demonstrated as a promising feedstock for co-gasification with biomass. Abstract: In this work, direct (air) co-gasification of refused derived fuel with biomass was demonstrated in an 80kWth pilot-scale bubbling fluidized bed reactor. The influence of the process operating parameters, namely average bed temperature between 785 and 829 °C, equivalence ratio between 0.21 and 0.36 and refused derived fuel weight percentage in the fuel mixture (0, 10, 20, 50 and 100 wt%) was analyzed. For the operating conditions used, the process was demonstrated as autothermal and operating under steady-state conditions, with no defluidization phenomena observed. The increase of the refused derived fuel weight percentage in the fuel mixture led to an increase of the methane and ethylene concentration in the producer gas and, consequently, an increase of the producer gas lower heating value, reaching a maximum value of 6.4 MJ/Nm 3 . In terms of efficiency parameters, cold gas efficiency was found between 32.6 and 53.5% and carbon conversion efficiency between 56.0 and 84.1%. A slight increase of the cold gas efficiency was observed with the increase of the refused derived fuel weight percentage in the fuel mixture. Thus, refused derived fuel co-gasification with biomass was shown as a highly promising process for the valorization of wastes as an energetic resource.